2016
DOI: 10.1159/000448247
|View full text |Cite
|
Sign up to set email alerts
|

Oral Drugs Related with Muscle Wasting and Sarcopenia. A Review

Abstract: Sarcopenia is a geriatric syndrome characterized by progressive and generalized loss of skeletal muscle mass and function. Reported prevalence of this geriatric syndrome, differs depending on the definition, the population and the method used to identify sarcopenia. The causes of sarcopenia are multifactorial, and can include genetic influence, immobility or disuse, endocrine factors, inflammation and nutritional deficiencies. These disorders involve an imbalance between anabolic and catabolic pathways that ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 85 publications
1
72
1
2
Order By: Relevance
“…Finally, regarding the number of medications, this reflects the patient's comorbidity burden (more medications indicate more co-morbidities). The accumulation of diseases and other clinical deficits is very much part of the very concept of frailty [8,22]; nonetheless, since, in our study, the number of medications showed an independent effect in the multivariate model, the possibility cannot be ruled out that certain medications or drug interactions could predispose individuals to frailty [23].…”
Section: Discussionmentioning
confidence: 54%
“…Finally, regarding the number of medications, this reflects the patient's comorbidity burden (more medications indicate more co-morbidities). The accumulation of diseases and other clinical deficits is very much part of the very concept of frailty [8,22]; nonetheless, since, in our study, the number of medications showed an independent effect in the multivariate model, the possibility cannot be ruled out that certain medications or drug interactions could predispose individuals to frailty [23].…”
Section: Discussionmentioning
confidence: 54%
“…However, our multivariate analysis showed that the number of medications had an independent effect on muscle strength; this would suggest that some medications may have an effect on muscle, as has also been suggested by a review on this topic [32]. Again, further studies are needed to explore in more detail the potential impact of certain medications on muscle wasting.…”
Section: Citationsupporting
confidence: 53%
“…Yang et al, 50 explained that Met activates the pathway involved in mitochondrial biogenesis and protects against apoptosis via the PGC-1α pathway. 51 22 Recently, Senesi et al, 29 indicated that Met regulates the principal molecular mediators of skeletal muscle hypertrophy and atrophy and is capable of inactivating the cellular mechanisms related to muscle injury.…”
Section: Discussionmentioning
confidence: 99%